Pasting behaviour of high impact ball milled rice flours and its correlation with the starch structure - Loubes, María Ana (2018)
The effects of rotational speed and milling time on pasting profile, particle size and morphology, damaged starch and gelatinization enthalpy of modified rice flours were analysed by response surface methodology to investigate the relationships among functional attributes and starch structure. Morphological changes were corroborated by scanning electron microscopy. Peak time (Pt), pasting temperature (PT), peak and final viscosities from rapid visco-analysis showed a significant decrease with increasing of milling severity. The reduction in final viscosity (FV up to 4770 mPa s), particularly for the refined flour fraction (volume median diameter, D50 < 140 µm), evidenced the poor capacity of damaged starch to bind water during heating step. In comparison with native flour, the modified flours presented higher values of damaged starch (DS 5.94–16.46%), and viscosities as well as lower values of gelatinization enthalpy (ΔH 4.67–0.71 J/g), Pt and PT denoting a lower resistance to shear stress and cooking. Such behavior is desirable in mixture design to enhance flour particles dispersion and to facilitate the interaction among food ingredients. Structural changes of starch were strongly associated to pasting behavior as it can be appreciated from the significant correlations founded: FV–DS, setback viscosity (SB)–DS, SB–D50, SB–ΔH. Planetary ball milling is a novel green method to obtain physically modified rice flours with distinctive characteristics regarding native flours, which could be well controlled by selecting suitable milling conditions. More studies should be required to expand the applications of the modified rice flours, in food and non-food products, with specific functional requirements.